PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SISWA KELAS IV SD NEGERI 002 KIYAP JAYA KECAMATAN BANDAR SEI KIJ - Neneng Kurniasih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low learning outcomes in Islamic Education (PAI) at SD Negeri 002 Kiyap Jaya. This condition was evidenced by the average student score of 65, with only 50% of students achieving learning mastery. This research employed classroom action research conducted in two cycles. The data used in this study included observations of teacher and student activities as well as students’ PAI learning outcomes. Based on the research results, the application of the Direct Instruction learning model was able to improve learning outcomes. This improvement was evidenced by: (a) increased teacher activity in each cycle. In the first cycle, the first meeting showed a teacher activity score of 12 (48.00%) in the “low” category, which increased to 17 (68.00%) in the second meeting with a “fair” category. In the second cycle, teacher activity further improved to 20 (80.00%) in the first meeting with a “good” category and reached 23 (92.00%) in the second meeting with a “very good” category. Student activity also increased across cycles. In the first cycle, the first meeting showed a student activity score of 11 (44.00%) in the “low” category, which increased to 16 (64.00%) in the second meeting with a “fair” category. In the second cycle, student activity increased to 19 (76.00%) in the first meeting with a “good” category and reached 22 (88.00%) in the second meeting with a “very good” category; and (b) improved PAI learning outcomes. Based on preliminary data, the average student score was 65 with a mastery percentage of 50%. In the first cycle, the average score increased to 69.25 with a mastery percentage of 70%, and in the second cycle, it further increased to 74.5 with a mastery percentage of 85%. Based on these findings, it can be concluded that the Direct Instruction learning model effectively improves PAI learning outcomes of students at SD Negeri 002 Kiyap Jaya.